Stereotactic partial breast irradiation in primary breast cancer: A comprehensive review of the current status and future directions - Takanen, Silvia; Pinnarò, Paola; Farina, Ilaria; Sperati, Francesca; Botti, Claudio; Vici, Patrizia; Soriani, Antonella; Marucci, Laura; Sanguineti, Giuseppe (Frontiers in Oncology, 2022)
In selected low-risk breast cancer (BC) patients, accelerated partial breast irradiation (APBI) may represent an alternative option to the whole breast irradiation (WBRT) to reduce the volume of irradiated breast and total treatment duration. In the last few years, preliminary data from clinical trials showed that stereotactic body radiotherapy (SBRT), which allows the administration of high doses per fraction, reducing the number of fractions and the dose to the surrounding normal tissues, in the context of APBI, may have the advantage to be less invasive compared to other APBI techniques, with preliminary good results in terms of local toxicity and cosmesis: the use of radiological findings from magnetic resonance (MR), fiducial markers at the level of the tumor bed and advanced new breast devices represent a fundamental support for both precise definition of the target and radiation planning.